Editorial Note - Shamsad Mortuza (Crossings)
CROSSINGS: A Journal of English Studies Department of English and Humanities University of Liberal Arts Bangladesh (ULAB) crossings@ulab.edu.bd Volume 15 | December 2024 | ISSN 2071–1107 | E-ISSN 2958-3179